Reformasi Sistem Hukum Atas Penanganan Kekerasan (Cultural Violence) Bagi Pekerja Perempuan - Ferdinan Manuel, Elkristi; Purba, Tri Putri (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2023)
Violence (cultural violence) has a different meaning from crime, violence has a broader meaning that includes direct, structural, and cultural violence. Violence against women workers is still occurring, recorded as many as 17 cases/day. This concern is coupled with the existence of power relations and culture that exist in Indonesia. Victims of violence, especially women, become worried about what they experience, considering the difficulty of getting justice and reporting on what is experienced. The handling of cases that occur is deadlocked, in fact, the company does not have adequate arrangements and structures to protect victims. For this reason, reform is needed within the scope of the legal system where the substance, structure, and legal culture to answer these problems. In this study, the author uses a socio-legal research methodology that can provide a comprehensive picture not only in the normative realm but the realm of real practice.